Research Trends of Branding In The Context of Eduation: A Bibliometric Analysis - Desi Rahmawati; Elsah Fanisyah; Uwes Anis Chaeruman; Suwarno Suwarno; Dirgantara Wicaksono (AL-ISHLAH: Jurnal Pendidikan, 2022)
One of the efforts to deal with the development of world globalization and competition in winning the market is to do branding. The purpose of this study is to identify trending topics about branding in the context of education. This research method using the bibliometric or quantitative approach for analyzing and mapping of information with the help of the Scopus database, VOSviewer for data visualization, and Tableau for data display. Based on our results of analysis, we have obtained 841 publications of branding and 163 branding publication documents related to branding in the context of education. Furthermore, we have defined the development of publications, the most leading countries, subject area, affiliations, source title, author, cited by sources, and kind of research topics related to branding strategies in the context of education. The study contributes by highlighting the trends of branding in the context of education. We also underline that the small number and instability of branding research in the educational context provide opportunities for branding research in the context of education. Despite the results of our analysis in this study, there are still weaknesses that still need to be considered. Further, future research should analyze relevant research clusters for emerging trends on branding in the context of education.